The Biogeographical Distribution of Soil Bacterial Communities in the Loess Plateau as Revealed by High-Throughput Sequencing - Liu, Dong; Yang, Yang; An, Shaoshan; Wang, Honglei; Wang, Ying (Frontiers in Microbiology, 2018)
The rigorous environmental stress of the severely eroded Loess Plateau may have promoted specific soil bacterial communities in comparison to other eco-environmental regions. In order to unmask the bacterial diversity and most influential environmental parameters, Illumina MiSeq high throughput sequencing of 16S rRNA from 24 representative soil samples collected across south-east to north-west transect of the Loess Plateau in northern Shaanxi, China was conducted. This high-throughput sequencing revealed approximately a total of 14,11,001 high quality sequences that classified into 38 phyla, 127 classes, greater than 240 orders and over 650 genera, suggesting a high bacterial diversity across the Loess Plateau soils. The 7 dominant groups were: Proteobacteria, Actinobacteria, Acidobacteria, Planctomycetes, Gemmatimonadetes, Chloroflexi and Verrucomicrobi (relative abundance of >5%). Soil pH and geographic longitude were all significantly positively correlated with both bacterial phylotype richness and phylogenetic diversity, respectively. Pairwise correlation analysis showed higher bacterial diversity at longitudinal gradients across 107°39′ to 109°15′ (south-east to north-west) in our studied Chinese loess zone. Variation partitioning analysis indicated significant influence of soil characteristics (approximately 40.4%) than geographical distance (at a landscape scale of ~400 km) that was responsible for 13.6 % of variation in bacterial community structure from these soils. Overall, contemporary soil characteristics structuring the bacterial community in Loess Plateau soils, more crucially than the spatial distances along the loess transect.